PROGNOSTIC SIGNIFICANCE OF MARKERS OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH CORONARY HEART DISEASE - Romanova, V.O.; Kuzminova, N.V.; Marchak, T.V.; Lozinsky, S.E.; Knyazkova, I.I.; Kulchytska, O.M.; Shkarivsky, Yu.L. (World of Medicine and Biology, 2022)
The data of 135 patients with an uncomplicated course of the disease and 27 with an unfavorable outcome were analyzed for assessment of the prognostic significance of markers of endothelial dysfunction as predictors of an unfavorable prognosis in patients with coronary artery disease. A prospective 2-year study showed that unfavorable cardiovascular events were observed significantly more often in the group of patients with coronary artery disease with an initial elevated level of biomarkers of endothelial dysfunction compared to individuals whose level of these biomarkers was within the reference values. The presence of myocardial infarction at the start of observation, decreased left ventricular ejection fraction
Keywords: endothelial dysfunction; coronary artery disease; patients’ prognosis; pregnancy-associated plasma protein A; soluble vascular cell-adhesion molecules; endothelin-1